Vision health disparities in blindness and visual impairment in Nigeria: A review of the Nigerian National Blindness and Visual Impairment Survey - Obinna F. Akano (African Vision and Eye Health, 2017)
Purpose: Blindness and visual impairment have become public health problems with prevalence increasing year after year. Nigeria, the most populated country in Africa, is also very diverse in terms of geographical location, ethnicity and culture. This study looks at and considers the vision health disparities in blindness and visual impairment in Nigeria using socio-demographic factors such as gender, geopolitical zones, place of residence and literacy.